Hubungan dislipidemia dengan kejadian stroke - Jun Edy Samosir Pakpahan; Bintang Hartati (Holistik Jurnal Kesehatan, 2022)
Background: Stroke is a loss of brain function caused by the cessation of blood supply to part of the brain, which results in impaired blood flow to the brain and can cause blockage (ischemic stroke) or bleeding (hemorrhagic stroke). Dyslipidemia and hyperlipidemia are risk factors for stroke, which is a lipid profile disorder characterized by a decrease or increase. The main lipid profiles were total cholesterol levels, triglyceride levels, HDL-C levels, and LDL-C levels.Purpose: To determine the relationship between cholesterol levels with ischemic (non-hemorrhagic) and hemorrhagic strokeMethod: A descriptive-analytic correlative observational study with a retrospective cross-sectional approach. The sampling technique using purposive sampling obtained as many as 30 samples. Processing and analysis of the data obtained using a program on a computer. Analysis of the data used is a univariate, bivariate, and multivariate analysis using contingency coefficients with a significance level of p <0.05.Results: Most respondents have high total cholesterol levels as many as 24 respondents (80%), and high triglyceride levels as many as 19 respondents (63.3%). High LDL-C levels were 16 respondents (53.3%), and high HDL-C levels were 16 respondents (53.3%). Calculation of statistical tests obtained the results of total cholesterol levels p=0.033 (p<0.05), triglyceride levels p=0.016 (p<0.05), LDL-C levels p=0.464 (p>0.05), HDL levels -C p=0.088 (p>0.05). Multivariate analysis using multiple logistic regression was the most correlated of the characteristics of dyslipidemia with the incidence of stroke in total cholesterol levels (p = 0.014).Conclusion: Dyslipidemia and dyslipidemia characteristics, namely total cholesterol and triglyceride levels have a significant relationship with the incidence of stroke. The most related characteristic of dyslipidemia is total cholesterol level with the incidence of stroke.Keywords: Cholesterol level; Ischemic (non hemorrhagic); Hemorrhagic strokePendahuluan: Stroke adalah kehilangan fungsi otak yang diakibatkan oleh terhentinya suplai darah kebagian otak, yang mengakibatkan gangguan aliran darah ke otak dan dapat menyebabkan penyumbatan (ischemic stroke) atau pendarahan (hemorrhagic stroke). Dislipidemia dan hiperlipidemia adalah suatu faktor risiko stroke yang merupakan suatu kelainan profil lipid yang ditandai dengan adanya penurunan atau peningkatan. Profil lipid yang utama adalah kadar kolesterol total, kadar trigliserida, kadar HDL-C, dan kadar LDL-C.Tujuan: Untuk mengetahui hubungan kadar kolesterol dengan stroke hemoragik and iskemik (non hemoragik).Metode: Deskriptif analitik korelatif dengan pendekatan cross sectional yang bersifat retrospektif. Teknik pengambilan sampel dengan purposive sampling didapatkan sebanyak 30 sampel. Pengolahan dan analisis data yang diperoleh menggunakan program SPSS. Analisa data yang digunakan adalah analisa univariat, bivariat dan multivariat menggunakan koefisiensi kontigensi dengan tingkat kemaknaan p<0,05.Hasil: Menunjukkan bahwa sebagian besar responden memiliki kadar total kolesterol tinggi sebanyak 24 reponden (80%), kadar trigliserida yang tinggi sebanyak 19 responden (63,3%), kadar LDL-C tinggi sebanyak 16 responden (53,3%), dan kadar HDL-C tinggi sebanyak 16 responden (53,3%). Perhitungan uji statistik diperoleh hasil kadar total kolesterol p=0,033 (p<0,05), kadar trigliserida p=0,016 (p<0,05), kadar LDL-C p=0,464 (p>0,05), dan kadar HDL-C p=0,088 (p>0,05). Analisis multivariat dengan menggunakan regresi logistic berganda yang paling berhubungan dari karakteristik dislipidemia dengan kejadian stroke ialah kadar total kolesterol (p=0,014).Simpulan: Dislipidemia dan karakteristik dislipidemia yaitu kadar total kolesterol dan trigliserida memiliki hubungan yang bermakna dengan kejadian stroke. Karakteristik dislipidemia yang paling berhubungan yaitu kadar total kolesterol dengan kejadian stroke.